Analisis Kompetensi Pedagogik Guru SD Dalam Penerapan Kurikulum Merdeka - Siddiqurahman Siddiqurahman; Musifuddin Musifuddin; Muhamad Ali (Educatio, 2026)
This study aims to analyze the pedagogical competence of elementary school teachers in implementing the Independent Curriculum. Pedagogical competence is a crucial aspect for the success of the learning process, especially in the context of implementing the new curriculum, which emphasizes differentiated learning, character building, and student independence. This study used a qualitative approach with a case study method. Data were collected through in-depth interviews, classroom observations, and document analysis with teachers in several elementary schools that have implemented the Independent Curriculum. The results indicate that most teachers understand the basic principles of the Independent Curriculum, but challenges remain in optimally integrating learning strategies that meet student needs. Several aspects of pedagogical competence that still need improvement include differentiated learning planning, the use of technology in learning, and adaptive formative evaluation. This study recommends increasing ongoing training and professional mentoring for teachers to strengthen their pedagogical competence to support the successful implementation of the Independent Curriculum.